The Role of The Agricultural Sector in Driving Sustainable Economic Development - Ary Andrian; Rudi Bratamanggala (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
The agricultural sector plays a strategic role in Indonesia's economic development through its contributions to Gross Domestic Product (GDP), employment absorption, and national food security. This study analyses the role of the agricultural sector in promoting sustainable economic development in Indonesia using secondary data from Statistics Indonesia (Badan Pusat Statistik, BPS) and the Ministry of Agriculture covering the period 2020–2024. A descriptive analysis method is employed to describe the agricultural sector's contribution to the national economy. The results show that the agricultural sector contributed 12.4% to national GDP in 2022, with a value reaching Rp1,134.5 trillion in 2023. The Farmer Terms of Trade (Nilai Tukar Petani, NTP) shows a positive trend, with the highest recorded value of 120.97 in February 2024, indicating improved farmer welfare. Rice production reached 53.63 million tonnes in 2023, with a harvested area of 10.20 million hectares. The agricultural sector has proven to be a resilient economic pillar, particularly during the pandemic period, recording growth of 1.84% in 2021. Agricultural technology development, production diversification, and improvements in competitiveness are identified as key factors in strengthening the agricultural sector's role in sustainable economic development.